Adherence to Practice Guidelines in the Implementation of Emergency Obstetric and Newborn Care in Referral Hospitals in Osun State, Nigeria - Abiola Olubusola Komolafe; Aanuoluwapo Omobolanle Olajubu; Omotade Adebimpe Ijarotimi; Oluwasayo Bolarinwa Ogunlade; Adekemi Eunice Olowokere; Omolola Oladunni Irinoye (SAGE Publishing, 2024)
Introduction While practice guidelines support clinical decision-making for optimal patient outcomes, there is often nonadherence to practice guidelines in implementing evidence-based interventions. Objectives This article aimed to assess adherence to practice guidelines in emergency obstetric and newborn care (EmONC) and the outcome of pregnancy in cases of obstetric complications in referral hospitals. Method The study employed a descriptive design. A purposive sampling technique was used to select the three tertiary hospitals and six out of nine state hospitals in Osun State. A data extraction form developed based on a fidelity framework was used to collect data on Adherence from 264 cases of obstetric complications. Descriptive statistics, such as frequency and percentage, and inferential statistics, such as chi-square, were done with the significance level set as p  < .05. Results Findings showed low adherence to practice guidelines in 70.8% of hemorrhage care, 52.0% of fetal distress care, 60.0% of prolonged obstructed labor care, and 44.4% of preeclampsia/eclampsia care. The study's findings also showed that 64.3% of cases of prolonged/obstructed labor, 54.9% of cases of fetal distress, and 46.7% of all cases of obstetric complications were referred out at the state hospitals. Neonatal mortality in state and tertiary hospitals was 3.7% and 21.7%, respectively, which was significantly different ( p  < .001). Conclusion There was low adherence to practice guidelines for the implementation of EmONC in state and tertiary hospitals, and a significant number of cases of obstetric complications were referred out in the state hospitals. The low adherence to practice guidelines and numerous referrals truncate the successful implementation of EmONC and hinder women and newborns from receiving optimal care for obstetric complications. There is a need to develop strategies that promote adherence to practice guidelines in implementing EmONC.